Survey, Culture, and Genome Analysis of Ocular Chlamydia trachomatis in Tibetan Boarding Primary Schools in Qinghai Province, China - Feng, Le; Lu, Xinxin; Yu, Yonghui; Wang, Tao; Luo, Shengdong; Sun, Zhihui; Duan, Qing; Wang, Ningli; Song, Lihua (Frontiers in Cellular and Infection Microbiology, 2017)
Trachoma, the leading infectious cause of blindness worldwide, is an ancient human disease. Its existence in China can be traced back to as early as the 27th century BC. In modern China, the overall prevalence of trachoma has dramatically reduced, but trachoma is still endemic in many areas of the country. Here we report that 26 (8%) of 322 students from 2 rural boarding schools of Qinghai province, west China, were identified as having ocular C. trachomatis infection; and 15 ocular C. trachomatis strains were isolated from these trachoma patients. Chlamydiae in 37 clinical samples were genotyped as type B based on ompA gene analyses. Three ompA variants with one or two in-between SNP differences in the second or fourth variable domain were found. C. trachomatis strains QH111L and QH111R were from the same patient’s left and right conjunctival swabs, respectively, but their ompA genes have a nonsynonymous base difference in the second variable domain. Moreover, this SNP only exists in this single sample, suggesting QH111L is a newly emerged ompA variant. Interestingly, chromosomal phylogeny analysis found QH111L clusters between a branch of two type B strains and a branch of both A and C strains, but is significantly divergent from both branches. Comparative chromosome analysis found that compared to sequences of reference B/TZ1A828/OT strain, 12 of 22 QH111L’s chromosomal genes exhibiting more than 9 SNPs have the best homology with reciprocal genes of UGT strains while 9 of 22 genes are closest to those of type C strains. Consistent with findings of UGT-type genetic features in the chromosome, the QH111L plasmid appears to be intermediate between UGT and classical ocular plasmids due to the existence of UGT-type SNPs in the QH111L plasmid. Moreover, the QH111L strain has a unique evolutionarily older cytotoxin region compared to cytotoxin regions of other C. trachomatis strains. The genome analyses suggest that the QH111L strain is derived from recombinations between UGT and classical ocular ancestors. This is the first study of culture and characterization of ocular C. trachomatis in Qinghai Tibetan areas.